Dealing with Foodborne Illness: Typhoid Fever, Salmonella Typhi - Karen Carver; Michael J. Mahovic; Renée M. Goodrich; Keith R. Schneider (EDIS, 2005)
Typhoid fever is a blood infection caused by consumption of food or water contaminated by the bacterium Salmonella enterica, subspecies enterica, serovar Typhi; commonly referred to as Salmonella typhi or S. typhi. Sometimes you will see the serovar capitalized, i.e., Salmonella Typhi. This is not to be confused with the many other members of the bacterial group Salmonella (often called “non-typhi Salmonella”), which invade the intestines to cause salmonella food poisoning, or salmonellosis. This document is FSHN0514, one of a series of the Food Science and Human Nutrition Department, UF/IFAS Extension. Original publication date August 2005.